A didatização de textos acadêmicos na educação de nível médio: uma proposta de intervenção a partir do gênero relatório - André Filho, Francisco (2023)
The present study aims to investigate the process and production of the report genre and its constituent elements, based on proposals for didactic sequences aimed at high sc hool and with focus on features social and co m m unicative characteristics of the respective genre, allowing students to act as competent text producers. and through a teaching proposal that considers the situational context of the scientific report g enre, while favoring the development of their possible language skills. Thus, when we recognize that the chosen genre is inserted in high school education, presenting itself in a context of teaching and learning of genres in the academic sphere, we defined a study based on this genre, as we noticed that this genre allows the use of writing and, consequently, reading at school/academy, as it describes the results or actions developed after a work activity related to academic language practices. Therefore, in order to achieve the purpose of our research, we propose an intervention based on the didactic sequences to speech discourse and writing forwards by Dolz, Noverraz and Schneuwly (2004), as well as on the concept of discursive genre defined by Bakhtin (200 0). Regarding the conception of language and teaching of writing, we consider the ideas of Antunes (2003), Marcuschi (2010) and Koch and Elias (2014). Regarding academic literacy, we focus on the ideas of Soares (2009), Dolz (2004), Leite and Pereira (2021 ), PCN’s (2001), BNCC (2018) and OCN’s (2006). With regard specifically to the scientific report genre, we used studies by Abreu Tardelli, Nascimento and Valezi (2018), Batista and Nascimento (2011), Bakhtin (2000), Beltrão and Beltrão (2005), Ribeiro and Souza (2017) and Ursi (2008). As methodological procedures, we opted for a research of a qualitative nature, in which, through action research and investigations of an interventionist nature, we had as participant’s students who attend the 3rd grade B of H igh s chool at a state full time pu blic school of Curral de Cima city PB, age d group of 16 and 22 years. Those students are included in a class composed of 22 (twenty two) students, of which 13 (thirteen) agreed to participate in our investigation and wer e authorized by their parents and/or guardians to collaborate with it. Of the 13 texts produced by the research subjects, six texts from the first version were selected and their respective six texts from the last version, that is, from the final rewrite, totaling 12 (twelve) texts destined for analysis. The results presented show that students, in addition to not mastering certain rules and procedures necessary for the writing process, for example, textual cohesion, also did not master or were even unaware of the elements that constitute the argumentation and informativeness of the textual genre investigated in the production of these texts. That said, we found that the students presented, from the first to the second version, changes related to the structu ral aspects of the genre. In addition, the didactic sequence procedure, especially the modules, contributed to the achievement of the expected results. Thus, it is an effective procedure for the teaching learning processes of textual production.